Palladium-catalyzed cyclization of a pyryne precursor to higher pyrenylenes - Popp, Dennis; Elbert, Sven; Barwig, Chantal; Petry, Julian; Rominger, Frank; Mastalerz, Michael (Angewandte Chemie. International edition, 2023)
The palladium catalyzed cyclotrimerization of ortho-silylaryl triflates as aryne precursors is meanwhile an established method to synthesize polycyclic aromatic hydrocarbons (PAHs) with triphenylene cores. During the palladium-catalyzed reaction of a pyrene with an o-silylaryl triflate moiety in the K-region higher homologues with central eight- and ten-membered rings (the pyrenylenes) were found, besides the expected trimer and a protocol was developed to isolate all members of this series. This unprecedented new class of PAHs was fully investigated by all means, including X-ray diffraction of single-crystals, UV/Vis and fluorescence spectroscopy and theoretical calculations. Supported by density-functional theory (DFT) calculations, a mechanism of all higher cyclooligomers is proposed.
Online veröffentlicht: 7. März 2023
Gesehen am 24.08.2023